STUDENTS’ ABILITY IN WRITING NARRATIVE TEXT: AN EXPERIMENTAL STUDY AT MA DARUSSIDIQIN NW MERTAK PAOK - mul muliadi (Lembaga Penelitian dan Pendidikan Mandala, 2019)
This research is aimed to measure the students’ ability in writing narrative text. The population of this research are all students of MA Darussiddiqien NW Martak Paok. The researcher takes 20% from the number of population; it’s mean that the researcher takes 40 students as the sample. This research is categorized into quantitative research. The data of this research is collected through tests. Looking at the result of analyzing the data, the students are able to write narrative text, the students’ mean score 68. There were 35 students (87,5%) who got good and there were 5 students (12,5%) who got fairly good, there were 36 students (87,5%) who got poor and there were none of students who category very good. The students’ level in writing narrative text was fair.